The Bone Keeper : a novel - Veste, Luca; Sastre, Elizabeth; Recorded Books, Inc. (Prince Frederick, Md. : Recorded Books, 2019)
He'll slice your flesh. Your bones he'll keep. The Bone Keeper's coming. And he'll make you weep. What if the figure that haunted your nightmares as a child was real? Twenty years ago, four teenagers went exploring in the local woods, trying to find the supposed home of the Bone Keeper. Only three returned. Now, a woman is found wandering the streets, horrifically injured, claiming to have fled the evil urban myth. And then a body turns up.
Compact disc.
In container (17 cm).
Title from container.
Narrated by Elizabeth Sastre.
Keywords: Police -- England -- Fiction -- Liverpool; Serial murder investigation -- Fiction -- England -- Liverpool; Women detectives -- England -- Fiction -- Liverpool; Audiobooks; Mystery fiction